STRUGGLE FOR BEING A CHAMPION IN HARRY POTTER AND THE GOBLET OF FIRE MOVIE (2005): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - DEWI., KARTIKA (2010)
The major problem of this study is to explain how the struggle for being a champion is reflected in Harry Potter and the Goblet of Fire movie. The objectives of this study are to analyze the structural elements of the movie and to analyze the character of Harry Potter based on individual psychological analysis developed by Alfred Adler. The researcher uses qualitative research in conducting the study. The data are based on primary data, the script of Harry Potter and the Goblet of Fire movie. While secondary data are reviews of movie those are collected from many sources like website, journal and others that have connection with the research. In analyzing the data, the writer applies two approaches. Those are structural analysis approach and individual psychological approach. Structural analysis approach is used to analyze the elements of the movie that consist of character and characterization, casting, setting, point of view, plot, theme, mise en scene, sound, editing, and cinematography. While individual psychological approach is used to analyze struggle for being a champion of Harry Potter that influences his personality. The results of the study are as follows. First, based on the structural analysis, it is clear that the movie that is directed by Mike Newell wants to give a message that is"A fair Tournament". Second, based on the individual psychological analysis, Harry Potter used all his own powers to become a champion in Triwizard tournament.